HUBUNGAN PENGETAHUAN DAN DUKUNGAN SUAMI DALAM PEMBERIAN ASI EKSLUSIF - Al Rahmad, Agus Hendra; Kartikasari, M. Nur Dewi; Kaluku, Khartini; Asma, Asma; Alamsyah, Putri Rahmah (Ensiklopedia of Journal, 2024)
Inadequate knowledge of husbands about exclusive breastfeeding will lead to low husband support, thus reducing the success of the exclusive breastfeeding process. This study aims to determine the relationship between knowledge and husband support in exclusive breastfeeding at Eria Bunda Hospital. This study used a quantitative analytic research design with a cross sectional study design. The sampling technique in this study was purposive sampling, so that the sample in this study was 70 respondents. The measuring instrument used was a questionnaire and data analysis using the chi square test. The results of the analysis showed that there was a relationship between knowledge (p value, 0.048) and husband support (p value 0.000) in exclusive breastfeeding at Eria Bunda Hospital. This study provides advice that health workers make efforts to improve the health services of medical personnel and nurses in health education through socialization and counseling on the importance of the breastfeeding process in order to increase husband's knowledge as an effort to increase husband's support in the breastfeeding process.Keywords: Knowledge, Husband Support, Exclusive Breastfeeding